Teaching English Activities for the Gifted And Talented Students (Conference Zone, 2022)
Individual work with gifted students plays an important role in the development of their intellectual abilities and creative abilities. Preparation for participation in Olympiads of various levels allows such children to show their best side. Teaching English in general educational institutions should be aimed not only at mastering the program material but also at identifying gifted children and organizing additional work with them